Palestine to Israel: Mandate to State, 1945-1948 (Volume II) : Into the International Arena, 1947-1948 - Penkower, Monty Noam (Academic Studies Press, 2019)
Seventy years after the creation of the State of Israel, Palestine to Israel: Mandate to State, 1945-1948 offers the definitive narrative of the achievement of Jewish sovereignty in the beleaguered Promised Land. Professor Monty Noam Penkower explores developments in Palestine and in the Arab states, including how the Palestine quagmire became a pawn in inter-Arab feuds; British and American responses both official and public; the role of Holocaust survivors; the context of the Cold War; and the saga as it unfolded in the corridors of the United Nations. Joining extensive archival research to a lucid prose, the two volumes offer a riveting conclusion to his Palestine in Turmoil and Decision on Palestine Deferred.
Keywords: Palestine -- History -- 1929-1948.; Israel -- History -- 1948-1967.; Palestine -- Histoire -- 1929-1948.; Israël -- Histoire -- 1948-1967.; HISTORY -- Middle East -- Israel & Palestine.; Israel; Middle East -- Palestine; 1929-1967; Arabs.; Cold War diplomacy.; Israel.; Israeli studies.; Jewish studies.; Judaism.; Middle East.; Middle Eastern studies.; Palestine.; Twentieth Century.; United Nations.; Zionism.; modern Jewish history.; nationalism.; Electronic books.; History